Analisis Penetapan Harga Jual Produk dan Volume Penjualan: Studi Kasus pada Rumah Makan Raja Ayam Kota Gorontalo - Nur’azizah Bungalo; Sahmin Noholo; Muliyani Mahmud (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the selling price of products at the Raja Ayam Restaurant in Gorontalo City and to determine the sales volume of products at the Raja Ayam Restaurant in Gorontalo City. The research method uses a survey method. The primary data source in this research is the owner of Raja Ayam Restaurant, Gorontalo City. The data obtained will be presented in tabular form and analyzed descriptively. The results of the research show that the product selling price at the Raja Ayam Restaurant in Gorontalo City is determined by calculating all costs which consist of fixed costs and variable costs. Raja Ayam Restaurant in Gorontalo City uses a selling price method that involves a mark-up of 30% of the total production costs. Thus, the selling price of the product is calculated by adding 30% of the total production costs. This strategy provides clarity in determining prices and includes the desired profit elements. In the main menu of Rumah Makan Raja Ayam, the price of each package or size of chicken is determined by applying a certain mark-up above the purchase price. By using the Mark-Up Pricing Method, these prices cover the profits desired by business actors and provide an overview of the pricing strategy used in the Raja Ayam business in Gorontalo City. The average sales volume of Rumah Makan Raja Ayam reaches around 1,229 packages of chicken every month, with sales of around 40 packages per day. The net income earned every month reaches Rp. Rp. 29,388,093.18, and daily net income is Rp. 979,603.11. Stable sales volume and good income reflect the positive performance and operational success of Rumah Makan Raja Ayam in Gorontalo City.